2000
DOI: 10.1080/02791072.2000.10400449
|View full text |Cite
|
Sign up to set email alerts
|

Blood Alcohol Content and Death from Fatal Injury: A Study in the Metropolitan Area of Sāo Paulo, Brazil

Abstract: This study analyzed 5,690 toxicological screenings carried out on blood and viscera of fatally injured victims at the Institute of Forensic Medicine in the Metropolitan area of São Paulo during 1994. The screenings analyzed correspond to 39.5% of all deaths due to injury in this metropolitan area during the same period. Almost half of the victims (48.3%) presented a positive blood alcohol content (BAC). The exact proportion however, varied according to the cause of death with 64.1% of victims of drowning testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
4
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
14
4
2
Order By: Relevance
“…In Brazil, studies have shown the relationship between the harmful effects of alcohol and driving. The review by Carlini Cotrim and Matta Chasin 16 showed a study conducted in four Brazilian cities where alcohol was present in 92% (n = 865) of victims of traffic accidents' blood in a typical week. Any amount of alcohol was found in 61% of the sample and 16.6% of the total sample had this value higher than 0.6 g/L.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies have shown the relationship between the harmful effects of alcohol and driving. The review by Carlini Cotrim and Matta Chasin 16 showed a study conducted in four Brazilian cities where alcohol was present in 92% (n = 865) of victims of traffic accidents' blood in a typical week. Any amount of alcohol was found in 61% of the sample and 16.6% of the total sample had this value higher than 0.6 g/L.…”
Section: Discussionmentioning
confidence: 99%
“…2 A study conducted in the city of São Paulo in 2000, with 1,808 students (993 from public schools and 815 from private schools), showed that 25% of them had at least one episode of binge drinking in the 30 days previous to the interview. 5 Young population is vulnerable to the negative, and very often, tragic consequences of the use of alcohol. 19 In the United States, alcohol is involved in the four leading causes of death among people between the ages of 10-24: traffi c accidents, unintentional injuries, homicides and suicide.…”
Section: Introductionmentioning
confidence: 99%
“…The indices varied from 36.2% in suicide victims to 64.1% in victims of drowning. 23 The authors of a study of victims of various non-fatal incidents of external causes, conducted in a trauma center in the city of São Paulo, reported a positive BAC in 28.9% of cases, the highest prevalence being among young, male victims of agression.…”
mentioning
confidence: 99%